Alumni giving of business executives to the alma mater: Panel data evidence at a large metropolitan research university - Albert A. Okunade; Phanindra V. Wunnava (Institute for the Study of Labor (IZA), 2011)
Charitable giving to public and private institutions of higher learning in the US is a growing major source of financing academic and support programs. The novel contribution of this research is the estimation of an econometric model of gift-giving alumni business executives of a large public urban university using 10,192 individual donor observations [that is, a panel of 392 donors for 26 years]. Our theoretically consistent empirical results reinforce the earlier research findings that male alumni in Greek social organizations gave significantly more. New insights unique to this study are that alumni individuals with the higher-order executive job titles (proxy for permanent income) of a Chief Executive Officer or President (relative to the lesser ranks) are significantly more charitable, and that the number of other gift-giving alumni and friends known to donors, and national athletic conference (basketball and football) championship wins are also highly statistically significant positive drivers of alumni annual giving to the comprehensive metropolitan research university. The resulting profile of gift-giving alumni business executives can be profitably used to more effectively target likely donors and raise cost-effectiveness of fundraising efforts in these times of fiscal austerity in higher education.
urn:nbn:de:101:1-201104084393
Keywords: I2; L3; 330; educational economics; educational finance; charitable donations; alumni giving of business executives; Hochschulfinanzierung; Spende; Führungskräfte; Schätzung; USA